2021
DOI: 10.1098/rsob.210168
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the topology of mammalian mitochondrial DNA

Abstract: The genome of mitochondria, called mtDNA, is a small circular DNA molecule present at thousands of copies per human cell. MtDNA is packaged into nucleoprotein complexes called nucleoids, and the density of mtDNA packaging affects mitochondrial gene expression. Genetic processes such as transcription, DNA replication and DNA packaging alter DNA topology, and these topological problems are solved by a family of enzymes called topoisomerases. Within mitochondria, topoisomerases are involved firstly in the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 221 publications
(309 reference statements)
0
11
0
Order By: Relevance
“…Indeed, mtDNA may be more susceptible to damage than nuclear DNA (nDNA) due to its proximity with the free radical-respiratory chain, the lack of protective histones lower fidelity of mitochondrial polymerase γ (POLG), and limited repair mechanisms [ 48 , 54 , 58 , 59 ]. As the mitochondrial producing genome, similar to its bacterial ancestors, has no introns and only one major non-coding region (NCR), any point mutation or deletion could disrupt cellular respiration [ 60 , 61 ]. Oxidative stress is considered as one of the factors negatively influencing mtDNA.…”
Section: Mitochondria In Human Gametes and Embryosmentioning
confidence: 99%
“…Indeed, mtDNA may be more susceptible to damage than nuclear DNA (nDNA) due to its proximity with the free radical-respiratory chain, the lack of protective histones lower fidelity of mitochondrial polymerase γ (POLG), and limited repair mechanisms [ 48 , 54 , 58 , 59 ]. As the mitochondrial producing genome, similar to its bacterial ancestors, has no introns and only one major non-coding region (NCR), any point mutation or deletion could disrupt cellular respiration [ 60 , 61 ]. Oxidative stress is considered as one of the factors negatively influencing mtDNA.…”
Section: Mitochondria In Human Gametes and Embryosmentioning
confidence: 99%
“…This creates a substantial delay between the initiation of leading- and lagging-strand synthesis from distinct sites on the genome. It is conceivable that this mechanism would generate the ssDNA gaps required for TOP3A to act as the sole decatenase in mitochondria ( 26 , 47 ). Such a model would be consistent with our results indicating that the loss of TOP3A results in the accumulation of hemicatenated replication termination intermediates ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Type II topoisomerase activities have been described in mitochondrial fractions ( 40–43 ), and later studies have suggested a mitochondrial localisation for either a truncated form of TOP2B ( 44 ), or full-length TOP2B and TOP2A ( 45 , 46 ). The exact roles and contributions of topoisomerases to maintaining mtDNA topology during mtDNA replication and transcription remain poorly understood ( 47 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mtDNA is organized in the form of nucleo-protein complexes termed nucleoids [18][19][20][21][22][23], which contain yet unde ned number of copies of double-stranded (ds) mtDNA. Biology of nucleoids is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…They oppose the processes of mitophagy and mtDNA degradation, establishing homeostasis. Other gene expression machinery and mtDNA repair proteins permanently exist within or are recruited to the nucleoid structure [18][19][20]23].…”
Section: Introductionmentioning
confidence: 99%